Pola Interaksi Sosial Penghuni “Lokalisasi’ Bukit Maraja Dengan Masyarakat Sekitar - LUCIE DEVIREDTRAVIA BATUBARA (Perspektif Sosiologi, 2012)
Abstract "Localization" is a community who interacting with each other. The research was in the village of Bukit Marihat, District of Mount Malela, Simalungun District. Research’s data retrieval is done by observation and interviews involving localization occupants and the surrounding community. The results of this study indicate the interaction is shaped “localization” Bukit Maraja occupants of cooperation, competition and tolerance. Cooperative relationship between residents of localization with the surrounding community pro who has social closeness as mutualy beneficial (symbiosis mutuality) is woven is traders and domestic servants who worked in localization of the occupants localization. This collaboration raises the tolerance around the existence of localization. But people around the counter didn’t interact with sex wokers and persuasive approach to warn residents of localization to behave, dress modestly. Keywords: Localization, cooperation, tolerance, conflict, mutual symbiosis.